Donavan's word jar - DeGross, Monalisa; Hanna, Cheryl (New York, NY : HarperCollinsPublishers, 1994)
When the jar that Donavan keeps his word collection in fills up, he finds a special way to give his words away and get something wonderful in return.
Keywords: Vocabulary; African Americans